Focality and extension in kinship : essays in memory of Harold W. Scheffler - Shapiro, Warren, 1941-; ANU Press (Acton, ACT : ANU Press, 2018)
When we think of kinship, we usually think of ties between people based upon blood or marriage. But we also have other ways--nowadays called 'performative'--of establishing kinship, or hinting at kinship: many Christians have, in addition to parents, godparents; members of a trade union may refer to each other as 'brother' or 'sister'. Similar performative ties are even more common among the so-called 'tribal' peoples that anthropologists have studied and, especially in recent years, they have received considerable attention from scholars in this field. However, these scholars tend to argue that performative kinship in the Tribal World is semantically on a par with kinship established through procreation and marriage. Harold Scheffler, long-time Professor of Anthropology at Yale University, has argued, by contrast, that procreative ties are everywhere semantically central, i.e. focal, that they provide bases from which other kinship ties are extended. Most of the essays in this volume illustrate the validity of Scheffler's position, though two contest it, and one exemplifies the soundness of a similarly universalistic stance in gender behaviour. This book will be of interest to everyone concerned with current controversy in kinship and gender studies, as well as those who would know what anthropologists have to say about human nature.
Part I. Introduction: Hal Scheffler's Extensionism in Historical Perspective and its Relevance to Current Controversies / Warren Shapiro and Dwight Read -- Part II: The Battle Joined. Hal Scheffler Versus David Schneider and His Admirers, in the Light of What We Now Know About Trobriand Kinship / Warren Shapiro -- Extension Problem: Resolution Through an Unexpected Source / Dwight Read -- Part III: Ethnographic Explorations of Extensionist Theory. Action, Metaphor and Extensions in Kinship / Andrew Strathern and Pamela J. Stewart -- Should I Stay or Should I Go? Hunter-Gatherer Networking Through Bilateral Kin / Russell D. Greaves and Karen L. Kramer -- Properties of Kinship Structure: Transformational Dynamics of Suckling, Adoption and Incest / Fadwa El Guindi -- Of Mothers, Adoption and Orphans: The Significance of Relatedness in a Remote Aboriginal Community / Victoria Katherine Burbank -- Part IV: Extensionist Theory and Culture History. Enhancing the Kinship Anthropology of Scheffler with Diachronic Linguistics and Centricity / Patrick McConvell -- Part V: Questioning Extensionist Theory. Why Do Societies Abandon Cross-Cousin Marriage? / Robert Parkin -- Toward Reinvigorating an Ethnolinguistic Approach to the Study of 'Kin Terms': A View from Nascent-based Zuni Relational Terminology / Linda K. Watts -- Part VI: Extensionist Theory and Human Biology. Creeping Plants and Winding Belts: Cognition, Kinship, and Metaphor / Bojka Milicic -- Kinship in Mind: Three Approaches / Doug Jones -- Do Women Really Desire Casual Sex? Analysis of a Popular Adult Online Dating/Liaison Site / Michelle Escasa-Dorne and William Jankowiak.
Prepublication record (machine generated from publisher information).
Includes bibliographical references and index.
Keywords: Scheffler, Harold W; Anthropology; Essays; Festschriften; Kinship; Anthropology; Philosophy & Religion; Society & Social Sciences; Australian; Electronic books